2017
DOI: 10.2214/ajr.16.17206
|View full text |Cite
|
Sign up to set email alerts
|

Role of Clinical Decision Tools in the Diagnosis of Pulmonary Embolism

Abstract: Pulmonary CT angiography is the imaging modality of choice for evaluating patients with suspected PE. Despite increased use of pulmonary CTA, the diagnostic yield for PE remains low. Study results suggest a potential benefit to the use of clinical decision tools in the diagnostic workup of suspected PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 126 publications
2
22
0
Order By: Relevance
“…Clinical decision rules such as Wells, Geneva, and PERC were created and designed to help clinicians risk‐stratify patients undergoing workup for possible PE. In particular, the PERC were designed to eliminate the need for PE testing if a patient scored zero out of eight criteria . We found that, even in an academic center, adherence to PERC did not seem consistent and a significant percentage of PERC‐negative patients had PE testing performed.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Clinical decision rules such as Wells, Geneva, and PERC were created and designed to help clinicians risk‐stratify patients undergoing workup for possible PE. In particular, the PERC were designed to eliminate the need for PE testing if a patient scored zero out of eight criteria . We found that, even in an academic center, adherence to PERC did not seem consistent and a significant percentage of PERC‐negative patients had PE testing performed.…”
Section: Discussionmentioning
confidence: 93%
“…Multiple clinical decision rules exist to aid the clinician in the risk stratification of patients with signs and symptoms that may be consistent with PE . One of the most utilized clinical decision rules is the Pulmonary Embolism Rule‐out Criteria (PERC) .…”
mentioning
confidence: 99%
“…In the cases where a PE is highly suspected or likely, it is preferred to proceed directly to imaging such as a computed tomography pulmonary arteriography (CTPA). The ease of obtaining it, combined with the high predictive value (92-96%), has placed CTPA as the dominant imaging modality for suspected PE [40]. In patients unable to receive iodinated contrast, a ventilation-perfusion (V-Q ) scan or a contrast-enhanced magnetic resonance angiography (MRA) may represent a valid alternative.…”
Section: Pulmonary Embolismmentioning
confidence: 99%
“…MRA has a sensitivity of 78% and specificity of 99%. This imaging study, however, relies on patient participation and compliance, and therefore a nontrivial proportion of studies will be inadequate to obtain sufficient level of diagnostic accuracy [40]. Once diagnosed, the treatment of PE involves systemic anticoagulation, with more invasive measures such as thrombolysis or embolectomy performed in patients with significant hemodynamic instability, respiratory decompensation, or acute right ventricular dysfunction [37].…”
Section: Pulmonary Embolismmentioning
confidence: 99%
“…Computed tomography pulmonary angiography (CTPA) is currently the preferred imaging modality for diagnosis of suspected pulmonary embolism (PE). With improved spatial and temporal resolution available with modern CT scanners, CTPA has high diagnostic accuracy in the detection of segmental and subsegmental PE (1)(2)(3). However, the high radiation dose associated with CTPA is still a concern, given the high prevalence of PE and widespread use of less-invasive imaging for clinical diagnosis (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%